Komunikasi Organisasi Pendidikan - Mesiono, Riduan Pohan (Pusdikra Publishing, 2021)
This research aims to find out how communication in education is a very important element in its position, in fact it has a very large role in determining the success of the education concerned. People often say that the level of an achievement of the quality of education is influenced by this communication factor, especially educational communication. Therefore, it is important for us to become skilled at communicating, and to know the principles of communication in both education and society. The research method used is literature study while the results of research Communication will be well established, if the ideas or ideas discussed are communicated in a deliberation between the communicator and the communicant, so that there is an understanding of information or everything that is the subject of the discussion which will lead to agreement and unity of opinion. The goals of a certain organization or institution will be realized and achieved maximally, if the communication process is carried out smoothly without any obstacles in it. Even though there are obstacles that arise, the communicators and communicants must look at them carefully to immediately solve the problems that trigger an obstacle. That way, the communication process carried out or in progress will run according to the wishes and desires to be achieved.